Robusta Powder Coffee Business Feasibility Study in Tanggamus Regency - Dwi Diana Sukmasari; Irmayani Noer; Ahfandi Ahmad (Journal of Business, Social and Technology, 2026)
Background: Tanggamus Regency is one of the largest producers of Robusta coffee in Lampung Province and holds significant potential for the development of coffee-based agro-industry focused on downstream processing. However, most farmers still sell their produce in the form of green beans, resulting in relatively low value-added economic outcomes and dependence on market price fluctuations. Objective: This study aims to analyze the business feasibility of establishing a Robusta ground coffee processing unit as an effort to increase the value added of local commodities and empower the local economy. Methods: This study uses a quantitative descriptive approach, analyzing market and marketing aspects, technical and production aspects, human resource management aspects, legal aspects, and financial aspects. Data were collected through field observations, interviews, and literature reviews related to the coffee industry. Results: The results indicate that market demand for locally processed coffee continues to rise, while the availability of raw materials in Tanggamus Regency is sufficient to support sustainable production. Financial analysis using Net Present Value (NPV), Internal Rate of Return (IRR), Net Benefit–Cost Ratio (Net B/C), and Payback Period (PP) indicators shows that the business is feasible and profitable to develop. Conclusion: The development of a Robusta ground coffee processing business in Tanggamus Regency is financially viable and strategically supports agricultural downstream processing. This business contributes to increasing the added value of local coffee commodities, improving farmers’ economic welfare, strengthening regional competitiveness, and supporting sustainable local economic development.